2020
DOI: 10.1371/journal.pone.0243062
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Lactobacillus paracasei HB89 mitigates PM2.5-induced enhancement of inflammation and allergic airway response in murine asthma model

Abstract: PM2.5 causes abnormal immune response and asthma in animals. In this study, a Balb/c mouse animal model was exposed to PM2.5 to induce asthma. Lactobacillus paracasei HB89 was fed at the same time, in order to observe whether L. paracasei HB89 mitigates respiratory tract allergies stimulated by PM2.5. The results showed that PM2.5 stimulated a significant increase in white blood cells and immunoglobulin (IgE) in OVA-induced allergic Balb/c mice, and IgE in the blood further triggered the release of histamine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…According to reports in recent years, the most commonly studied probiotics are Lactobacillus and Bifidobacterium . Their protective effects in animal models of respiratory virus infection have been well established 29 . For example, orally administered Lactobacillus , including Lactobacillus casei , Lactobacillus rhamnosus , Lactobacillus gasseri , Lactobacillus pentosus , Lactobacillus plantarum , Lactobacillus brevis , Lactobacillus johnsonii , Bifidobacterium breve 155 , and Bifidobacterium longum 180 , protected all the mice from influenza-virus-induced pathology and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports in recent years, the most commonly studied probiotics are Lactobacillus and Bifidobacterium . Their protective effects in animal models of respiratory virus infection have been well established 29 . For example, orally administered Lactobacillus , including Lactobacillus casei , Lactobacillus rhamnosus , Lactobacillus gasseri , Lactobacillus pentosus , Lactobacillus plantarum , Lactobacillus brevis , Lactobacillus johnsonii , Bifidobacterium breve 155 , and Bifidobacterium longum 180 , protected all the mice from influenza-virus-induced pathology and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria can also be used as a therapeutic tool, and this applies also to PM-induced lung allergic inflammation. Lin et al (2020), showed that Lactobacillus paracasei decreased the type 2 allergic response induced by OVA and PM, by decreasing the IgE levels, cytokines IL-4, IL-5, IL-13, and histamine [127]. This was confirmed by Nam et al (2020), who also showed that probiotics can protect against PM-induced airway inflammation [128].…”
Section: Particulate Mattermentioning
confidence: 98%
“…Recent studies were mostly focused on probiotics, of which Lactobacillus and Bifidobacteria were the most common. The protective effects of these two bacteria in viral respiratory tract infections have been verified in animal models [33]. For example, oral administration of Lactobacillus, such as Lactobacillus casei, Lactobacillus rhamnosus, Lactobacillus gasseri, Lactobacillus pentosus, Lactobacillus plantarum, Lactobacillus brevis, Lactobacillus johnsonni, Bifidobacterium breve 155, or Bifidobacterium longum 180 could protect mice from flu virus-induced pathology and mortality.…”
Section: Respiratory Tract Infection and Gut Microorganismsmentioning
confidence: 99%